Finiteness theorem for topological contact equivalence of map germs - Birbrair, Lev; Costa∗, João Carlos Ferreira [UNESP]; Fernandes, Alexandre (Department of Mathematics, Hokkaido University, 2009)
Let Pk (n, 2) be the set of all real polynomial map germs f = (f1, f2): (Rn, 0) → (R2, 0) with degree of f1, f2 ≤ k. The main result of this paper shows that the set of equivalence classes of Pk (n, 2), with respect to topological contact equivalence, is finite. © 2009 by the University of Notre Dame. All rights reserved.
Keywords: Finiteness theorem; Topological contact equivalence